ORGANIC FRUIT PRODUCTION OF GUAVA CV. L-49 IN GANGETIC ALLUVIAL PLAIN OF WEST BENGAL - KAUSHIK DAS; D. ROY; D. SENGUPTA; P. DATTA (The Bioscan, 2015)
Ten treatments of Vermicompost and FYM alone and in combinations were applied on 6 years old guava plant at farmer’s field, Gayeshpur, Nadia, West Bengal during 2012-13. Combined application of Vermicompost @ 5 kg/ plant + FYM @ 20 kg/plant (T6) was found best as compared to other treatments which significantly increased the physico-chemical attributes of guava where highest fruit length (8.42cm), diameter (7.10cm), fruit weight (140.42g) and pulp weight (96.38g) was recorded, whereas regarding chemical attributes viz. maximum TSS (10.40 oBrix), total sugar (7.39%), reducing sugar (4.11%), Vitamin C (163.41 mg/100g of pulp) and least acidity (0.21%) was obtained in this treatment while chemical fertilizer (T9) recorded maximum acidity (0.39%). Leaf minerals (N, P and K) were also affected by application of different organic nutrients with maximum nitrogen (1.48%) and potassium (1.11%) obtained from Vermicompost @ 5 kg/plant + FYM @ 20 kg/plant while Vermicompost @ 10 kg/plant + FYM @ 20 kg/plant recorded maximum leaf P (0.40%) content. Thus among the different treatments Vermicompost @ 5 kg/plant + FYM @ 20 kg/plant (T6) application was found to be best which significantly improve the soil health, fruit quality, leaf mineral content and an increased yield by 14.12%.